2023
DOI: 10.1371/journal.pone.0291732
|View full text |Cite
|
Sign up to set email alerts
|

The effects of plant-based dietary patterns on the risk of developing gestational diabetes mellitus: A systematic review and meta-analysis

Yu Zhu,
QingXiang Zheng,
Ling Huang
et al.

Abstract: Background The worldwide prevention of gestational diabetes mellitus (GDM) is a significant health challenge. Plant-based dietary patterns are a series dietary habits that emphasized foods derived from plant sources more and from animal foods less. Now, no consensus exists on the effects of plant-based dietary patterns on the incident of GDM. Objective This study aimed to estimate the effects of plant-based dietary patterns on the risk of developing GDM. Methods This systematic review was conducted followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This was in accordance with a sub-analysis of women with the same BMI class within another publication 36 . Two meta-analyses specified the type of diet showing that a plant-based approach, respectively a Mediterranean diet significantly reduced GDM 40 41 . One SR investigating a low-glycemic index diet found a decreased rate of LGA children 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in accordance with a sub-analysis of women with the same BMI class within another publication 36 . Two meta-analyses specified the type of diet showing that a plant-based approach, respectively a Mediterranean diet significantly reduced GDM 40 41 . One SR investigating a low-glycemic index diet found a decreased rate of LGA children 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of sugar-sweetened drinks, potatoes 71 , animal fat and cholesterol 72 , high glycemic load and low-cereal fiber diets 73 are associated with an increased risk for GDM. Alternatively, a high-fiber diet 73 , a plant-based diet 40 , a Mediterranean diet 41 , intake of vegetables, a substitution of red meat for poultry, fish, or legumes 74 and of potatoes by vegetables 71 and adherence to “healthful” dietary patterns 75 are also associated with a lower risk of GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary macronutrients have also been linked to increasing GDM risk including the consumption of low fiber, high glycemic index diets [12] and low carbohydrate, high-fat diets [13]. Of late a whole host of dietary strategies have been or are being studied to investigate potential links with alterations in GDM risk, including variations of the Mediterraneanstyle diet [14,15], high-fiber diets [16], diets with high complex carbohydrate contents [17], plant-based dietary patterns [18], diets high in probiotic yogurt contents [19], and diets with high colorful fruit and vegetable contents [20]. Further, observational dietary studies have reported associations between GDM risk and protein intake in early pregnancy (higher risk with increased early animal protein intakes and lower risk with increased early plant protein intakes [21]).…”
mentioning
confidence: 99%